Wordwall Game as an Interactive Medium in Arabic Vocabulary Acquisition for Novice Learners - Najib, Ahmad Farhan Rif'an; Setiyadi, Alif Cahya; Mahmudi, Ihwan; Muhyiddin, Luthfi (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
Vocabulary acquisition remains one of the key challenges in learning Arabic among novice learners, particularly when instruction relies heavily on conventional lecture-based and rote memorization methods. These traditional approaches often result in low learner motivation and limited retention. This article presents the evaluation of the effectiveness of Wordwall: Arabic Games for Arabic novice learners or beginners as an interactive medium to enhance Arabic vocabulary mastery. A quantitative experimental method was employed using a pretest-posttest control group design. The participants consisted of 30 third-grade KMI students at Pondok Modern Darussalam Gontor, divided equally into an experimental group (n=15), which received instruction using Wordwall games, and a control group (n=15), which used conventional teaching methods. The data were analyzed using an independent sample t-test to determine significant differences in vocabulary mastery. The results revealed that the experimental group showed a statistically significant improvement compared to the control group (Sig. 0.000 < 0.05). Furthermore, questionnaire responses indicated higher levels of engagement and motivation among students in the experimental group. These findings suggest that game based digital tools such as Wordwall can serve as effective and engaging alternatives in Arabic vocabulary instruction for beginners.